Structural and swelling study of Karharbari coal with various combinations of solvent. (7th July 2021) - Jaiswal, Yash; Pal, Sunder Lal; Kush, Lav
Swelling kinetics of Karharbari coal in various combinations of solvents such as T/PY, T/PNT, T/FLT, T/ANT, T/MNAP, T/NAP, T/FL, T/D were studied using the solvent swelling technique. The values of equilibrium swelling ratio Qe and diffusional exponent n were calculated to find the nature of diffusion while changing temperature and solvent combinations. Results conclude that with an increase in swelling temperature the nature of swelling shifts from relaxation diffusion controlled to the Fickian diffusion controlled. The activation energies with different solvents were also calculated to suggest the actual energy barrier for swelling of coal. Structural changes in coal due to penetration of solvents were also determined by using FTIR analysis of all combinations of solvents. The resultant energy barriers for swelling of coal were found to be hydrogen bond (H-bond). This work also includes the percentage extraction of H-bond obtained for all combinations of solvents. The results obtained firmly conclude that the solvent combination of tetralin and pyrene (T/PY) is the best combination of solvents for the pretreatment of coal for coal liquefaction. [Received: October 24, 2019; Accepted: July 30, 2020]